a EVALUASI TATA KELOLA SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) TAHUN AJARAN 2022/2023 BERBASIS COBIT 5 DI SMK NEGERI 4 PALEMBANG - Syahputra, Heri Akwan; Sutabri, Tata (LPPM UNIVERSITAS BINA INSAN, 2023)
This research aims to evaluate the level of maturity of information technology (IT) governance in the implementation of the New Student Admissions (PPDB) information system services at SMK Negeri 4 Palembang for the 2022/2023 academic year. The method used is a mixed quantitative and qualitative method using questionnaires, interviews and document studies. The focus of this research is on several COBIT 5 domains including, EDM4, APO7, and BAI4. Data sources were obtained from the Principal of SMK Negeri 4 Palembang, Head of TU and Administrative staff of SMK Negeri 4 Palembang, Chair of the PPDB Executive Committee of SMK Negeri 4 Palembang, and Members of the PPDB Executive Committee of SMK Negeri 4 Palembang. The research analysis was carried out using a descriptive interpretive method based on COBIT 5. The research results show that the level of IT governance maturity in the PPDB service at SMK Negeri 4 Palembang is currently at level three (established). These results are compared with the expected level of maturity, namely level five (optimizing), from the results of this comparison the gap value is obtained. The gap value is used to formulate recommendations for improvement. To improve IT governance, it is recommended that institutions prepare competent human resources, as well as document every evaluation, direction and monitoring activity in managing the implementation of PPDB SMK Negeri 4 Palembang.